Global supply chain risk management: an approach on how global firms manage the complexity of their worldwide operations - Moraes, Perycles dos Santos (2017)
The global supply chain risk management field is crucial for the supply chain sustainability, however, it is yet poorly explored, especially when it comes to matching the literature studies with empirical observations. The complexity inherent to these supply chains turn the studies and analyzes of risk-related issues, such as risk exposure, perception and its management strategies, time-to-time more significant to building a resilient and sustainable chain. In order to develop a coherent and relevant contribution for the literature, this dissertation provides three case studies of three companies from different industries. These case studies provide a qualitative approach of the firms’ risk perception and their management strategies. After the exposure of each of the three firms supply chain scenario, it is developed an analysis of the case studies, taking into account what is suggested and advised by former researchers in this field. The findings of this research indicate that the three companies do not dominate the existing supply chain risk management theoretical framework, nor fully apply risk management dynamics and strategies proposed by researchers. Instead, on average, they know in detail what are the risk-related events likely to have impacts onto their supply chains; moreover, their risk management strategies seem to be effective on both avoiding impacts and overcoming barriers and disruptions. On the other hand, the researchers’ and companies’ mindset converge on betting on cooperation/collaboration and communication/information sharing as builders of visibility, flexibility and agility into a supply chain, finally improving its resilience and reducing its risk exposure.